TRANSFORMASI BUDAYA UNTUK MEMPERBAIKI KINERJA PEMBANGUNAN - Pramono, Joko (Universitas Slamet Riyadi, 2008)
ABSTRACT To do working, each and every person wishes competent production to taking place its life, to fulfill requirement and his desire. So also in the world of trading, obtaining advantage represent target the core important. However, searching advantage may not tip of greed by raging so that can cause to harm others. Every transaction must be done admittedly and is fair. Price specified and agreed on according to quality of service or goods which is transaction. Thereby, searching advantage mean not merely profiting own self, but also profit others. Keywords: transformation, cultural, development performance